A reliable and valid tool to assess the sexual acceptability of contraceptive methods - Lahoz-Pascual, Isabel; Jurado-Lopez, Ana Rosa; Juárez-Vela, Raúl; Santolalla-Arnedo, Iván; Ruiz de Viñaspre-Hernández, Regina; Repollés-Lasheras, Sira; Tejero Sancho, Susana; Diaz-Vega, Miguel; Lou-Mercade, Ana Cristina; Mendoza-Ladrón de Guevara, Nicolás (Frontiers in Public Health, 2024)
Adequate identification of the sexual acceptability of contraceptive methods is key for designing health promotion interventions, assessing their impacts, and increasing their effectiveness. This study aimed to develop and validate a questionnaire to explore the preferences of women depending on their epidemiological characteristics and their partner relationships -the Sexual Acceptability of Contraceptive Methods Questionnaire (in Spanish, Aceptabilidad Sexual de los Métodos Anticonceptivos (ASMA)).Psychometric validation was conducted using Exploratory Factorial Analysis (EFA) and confirmatory factor analysis (CFA). The reliability of the final version of the questionnaire was explored using Cronbach's alpha and McDonald omega to estimate internal consistency.A three-factor model was identified. Factor 1 (explaining 28.32% of the model) corresponds to questions concerning the use and placement of the contraceptive and includes 6 items; Factor 2 (explaining 24.23%) corresponds to other factors that affect the relationship such as bleeding and side effects of the contraceptive method and includes 10 items; and Factor 3 (explaining 18.94%) corresponds to the couple relationship and includes 8 items.The ASMA questionnaire provides a valid and reliable tool for assessing the sexual acceptability of various contraceptive methods. This instrument gathers data that provide information on various aspects of women's sexuality, health, education, and beliefs, all of which can determine the preference for one contraceptive method over another. Moreover, the tool can help to identify profiles of women who have different preferences when selecting a particular method.